CONVENTIONAL ENERGY EFFICIENT ROUTING PROTOCOLS IN WIRELESS SENSOR NETWORKS - AL-RAWI, Muaayed F. (Applied Computer Science, 2020)
Wireless sensor network is a significant piece of wireless communication.It is a gathering of an enormous number of sensor nodes that are set in remote spots. The sensors have ability to do a typical undertaking. So energy exhaustion plays a significant job in keeping up a stable network. To build the system lifetime, a different energy effective algorithm is required which expands the network lifetime and makes the network more energy productive. For the augmenting, the lifetime of the network diverse routing technique has been utilized which help in expanding the lifetime of the network. This article portrays the diverse routing protocol which helps in energy efficient routing in a wireless sensor network.